City-regions in prospect? : exploring points between place and practice - Jones, Kevin Edson, 1973-; Lord, Alex, 1961-; Shields, Rob, 1979- (McGill-Queen's studies in urban governance, 2015)
"City-Regions in Prospect? Exploring the Meeting Points Between Place and Practice is a collection of essays and case studies that explore the "city-region" as both an evolving concept and a growing area of experiential knowledge. At the book's most basic level, it explores the "city-region" as a concept that captures the growing relevance and importance of cities in a rapidly urbanizing world. Looking more specifically at cities in Canada, the US, and England (Ottawa, Calgary, Manchester, Sheffield, for example), Jones et al outline how the city constructs and governs itself to respond to global needs, the logic behind this development, and the consequences involved in such aspirations. It sketches out new pathways for thinking about and acting upon municipal growth and governmental expansion to the effect of providing a better understanding of both the relationship between concepts and practice, and the actual interplay between the "city-region" and the global arena."--